2020
DOI: 10.1038/s41598-020-58876-w
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mouse model of TGFBI-R124C corneal dystrophy using CRISPR/Cas9-mediated homology-directed repair

Abstract: Mutations in transforming growth factor-beta-induced (TGFBI) gene cause clinically distinct types of corneal dystrophies. To delineate the mechanisms driving these dystrophies, we focused on the R124C mutation in TGFBI that causes lattice corneal dystrophy type1 (LCD1) and generated novel transgenic mice harbouring a single amino acid substitution of arginine 124 with cysteine in TGFBI via ssODNmediated base-pair substitution using CRISPR/Cas9 technology. Eighty percent of homozygous and 9.1% of heterozygous T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A granular corneal dystrophy type 2 mouse model was established via R124H mutation of Tgfbi and cross-sectional studies in this model revealed that genotype and age were associated with the incidence of corneal opacity [ 39 ]. The Tgfbi R124C mutant mouse model was established via CRISPR/Cas9 and is characterized by corneal opacity owing to the accumulation of mut-TGFBI and delayed epithelial wound healing similar to that observed in human patients with R124C LCD; though this model might not be a reliable as a LCD1 model due to the lack of amyloid deposition [ 40 ]. Currently, to the best of our knowledge, no animal models of human TBCD are available.…”
Section: Discussionmentioning
confidence: 99%
“…A granular corneal dystrophy type 2 mouse model was established via R124H mutation of Tgfbi and cross-sectional studies in this model revealed that genotype and age were associated with the incidence of corneal opacity [ 39 ]. The Tgfbi R124C mutant mouse model was established via CRISPR/Cas9 and is characterized by corneal opacity owing to the accumulation of mut-TGFBI and delayed epithelial wound healing similar to that observed in human patients with R124C LCD; though this model might not be a reliable as a LCD1 model due to the lack of amyloid deposition [ 40 ]. Currently, to the best of our knowledge, no animal models of human TBCD are available.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent literature survey, Zhang (2021) found that at least a dozen animal models have been generated using CRISPR/Cas genome editing technology. These include mouse, rat, pig, and rabbit models for studying various human diseases, including human non‐small‐cell lung cancers (NSCLCs) ( Maddalo et al, 2014 ), hepatocellular carcinoma (HCC) ( Liu et al, 2017 ), Hutchinson-Gilford progeria syndrome (HGPS) ( Liu ZQ et al, 2018 ), corneal dystrophy ( Kitamoto et al, 2020 ), and X-linked dilated cardiomyopathy (XLCM) ( Liu ZQ et al, 2018 ). Fujihara et al (2020) successfully created a rat model by using CRISPR/Cas9 genome editing for studying complex behavioral changes during schizophrenia.…”
Section: Wide Use Of Crispr/cas In Clinical and Preclinical Researcmentioning
confidence: 99%
“…73 Generating R124C mutation in TGFβl using CRISPR/Cas9-mediated homology-directed repair mechanism in zygotes of C57BL/6Ncr mice a novel transgenic mice model was generated mimicking human LCD. 74…”
Section: Crispr Editing In Corneal Dystrophiesmentioning
confidence: 99%
“…Using Cas9/gRNA (px 458) plasmid and a single-stranded HDR donor template, R124H mutation was corrected with a higher gene correction efficiency of 20.6% in heterozygous cells and 41.3% in homozygous cells with no detectable off-target effects 73 . Generating R124C mutation in TGFβl using CRISPR/Cas9-mediated homology-directed repair mechanism in zygotes of C57BL/6Ncr mice a novel transgenic mice model was generated mimicking human LCD 74 …”
Section: Crispr Gene Editing In the Corneamentioning
confidence: 99%